2008
DOI: 10.1128/jb.00682-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of Premature Stop Codons in Bacterial Evolution

Abstract: When the stop codons TGA, TAA, and TAG are found in the second and third reading frames of a protein-encoding gene, they are considered premature stop codons (PSC). Deinococcus radiodurans disproportionately favored TGA more than the other two triplets as a PSC. The TGA triplet was also found more often in noncoding regions and as a stop codon, though the bias was less pronounced. We investigated this phenomenon in 72 bacterial species with widely differing chromosomal GC contents. Although TGA and TAG were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…The relationship between stop codon frequency and G-content, or GC-content as reported previously [14], is one of the most striking and unambiguous patterns in bacterial genome composition (Figure 1). Here, we have developed a simple model that captures all of the major observations of stop codon distribution across bacterial genomes.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The relationship between stop codon frequency and G-content, or GC-content as reported previously [14], is one of the most striking and unambiguous patterns in bacterial genome composition (Figure 1). Here, we have developed a simple model that captures all of the major observations of stop codon distribution across bacterial genomes.…”
Section: Discussionsupporting
confidence: 79%
“…Firstly, translation termination efficiency may be nucleotide context dependent [9-13]. Second, TAG and TGA stop codon frequencies in bacterial genomes with different GC-contents are strikingly different (see Figure 1 in [14]), such that TGA frequency increases with genomic GC-content while TAG is GC-content independent. Here, we study stop codon frequency and evolution in bacterial genomes to gain an understanding of whether or not stop codons are used indiscriminately without any fitness costs.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence analysis of STY1365 showed the presence of a premature stop codon (TGA) within its single TM domain, suggesting the disruption of this segment, and consequently this protein will not be inserted within the bacterial membrane. The frequency of use of TGA as a premature stop codon in bacterial genomes increases with the increase in GC content, a classical feature of genomic regions acquired by horizontal transfer (Wong et al , 2008). This is in accordance with the genomic location of STY1365, which is part of a genomic island (GICT18/1) with high GC content compared with whole genome of S .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we detected the presence of a protein in the inner membrane of S. Typhi ($17 kDa) consistent with the molecular weight of STY1365 protein product plus FLAG tag, suggesting that STY1365 is fully translated. It has been reported that some phage genes containing TGA premature stop codon can be hopped by ribosomes, allowing protein synthesis (Goldman et al, 2000;Wong et al, 2008;Vakhrusheva et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The 49 Rickettsia genomes available in Ensembl Bacteria (release 22) [32] have small chromosome sizes (range 0.86-1.82 Mb; mean 1.23Mb), low %GC contents (mean 31.7%) and reduced coding capacities (mean 76%). Low %GC contents are important in this context, as alternative-frame premature stop-codons are more prevalent in AT-rich genomes, which are hypothesised to serve as error-correcting sequences to minimise the effect of deleterious frameshift mutations [33]. The genomes of both M. leprae [13] and S. glossinidius [24,34] have coding capacities of only 50%, suggesting there has not been sufficient evolutionary time or selective pressure for non-coding regions to be removed.…”
Section: Box 1 Intracellular Bacteria Genome Evolutionmentioning
confidence: 99%